Comparison of linear control methods for an AMB system - Grega, Wojciech; Piłat, Adam (Zielona Góra: Uniwersytet Zielonogórski)
The contactless nature of active magnetic bearings brings about many advantages over the conventional bearing while industrial real-time applications are often limited by the significant complexity of control algorithms. This paper presents the application of an LQ controller to an active magnetic bearing system (AMB).
Keywords: active magnetic bearing; real-time control; modelling; LQ control; control performance